Pemberdayaan Masyarakat melalui Tradisi Malam Nishfu Sya’ban: Membangun Lembar Baru dengan Nilai Religius - Moh. Mahfud; Abd Kholik (LP3M IAIFA Kediri, 2025)
Nishfu Sya’ban Night is a significant moment in Islamic tradition, holding various spiritual virtues. This report discusses the importance of utilizing Nishfu Sya’ban Night to enhance religious values and the quality of worship among the community, particularly in Branta Pesisir Village. A Participatory Action Research (PAR)-based program was implemented to raise awareness and understanding of this special night, strengthen Islamic brotherhood, and prepare residents spiritually for Ramadlan. Through a series of activities, such as Yasin recitation, communal prayers, lectures, and interactive discussions, there was a significant improvement in the quality of worship, community involvement in religious activities, and social solidarity. The program’s positive impact was evident in the residents’ enthusiasm to continue religious traditions on other Islamic occasions. Nishfu Sya’ban Night serves as a strategic moment to strengthen relationships with Allah SWT and fellow humans, ultimately fostering positive spiritual transformation in the community’s life.